Georgian-Ossetian conflict in August 2008 in the light of existing international rules - M N Kuznetsov (RUDN Journal of Law, 2012)
The article examines four facts that took place during the Georgian aggression against South Ossetia and Abkhazia from the point of international law. It presents the author’s view on the assessment of these events and proposes a number of practical measures for the exhaustion of the conflict.